Research of Tooth Cutting Theory and Milling Test on Small Module Spiral Bevel Gear - Bingyi Chui; Hua Zhang; Jianjun Yang (Jixie chuandong)
The processing of traditional small module spiral bevel gears is duplex spread-blade method， on the specialized gear milling machine. The gear and pinion are generated normally by the method of duplex， which has high processing efficiency， but the meshing quality on their surface is controlled in difficulty， which fundamentally limits the improvement of its transmission performance. For the bad contact zone of spiral bevel gears with duplex processing， the gear machining parameters are modified and optimized by using the TCA technology， thus the contact condition and meshing quality of the gear pair are improved. This can not only ensure the production efficiency of common modulus spiral bevel gear which is machined by duplex method， but also improve the meshing quality of the gear pair.